Distinguishing features of Lycium L. species (family Solanaceae) distributed in Egypt based on their anatomical, metabolic, molecular, and ecological characteristics - Ragab, Osama G.; Mamdouh, Diaa; Bedair, Ramadan; Smetanska, Iryna; Gruda, Nazim S.; Yousif, Sawsan K. M.; Omer, Rihab M.; Althobaiti, Ashwaq T.; Abd El-Raouf, Hany S.; El-Taher, Ahmed M.; El-Sayed, Ashraf S.; Eldemerdash, Marwa M. (Frontiers in Plant Science, 2023)
Among 70-80 species of Lycium genus (Family Solanaceae) disjunct distributed around the world, only 3 species are frequently distributed in different locations in Egypt. Regarding the morphological similarities between the 3 species, the need for alternative tools for distinguishing arises. Thus, the objective of this study was to revise the taxonomical features of L. europaeum L., L. shawii Roem. & Schult., and L. schweinfurthii var. aschersonii (Dammer.) Feinbrun., considering their anatomical, metabolic, molecular, and ecological characteristics. Besides the anatomical and ecological features, DNA barcoding through ITS sequencing and SCoT markers were performed for molecular characterization. Furthermore, the metabolic profiling of the studied species was obtained based on GC-MS. The observed anatomical features of the adaxial and abaxial epidermal layers, type of mesophyll; crystals, number of palisade and spongy layers; and the vascular system showed variations between the studied species. Otherwise, the leaves’ anatomy showed isobilateral structure in the studied species without distinct differences. The species were molecularly identified in terms of ITS sequences and SCoT marker where ITS sequences were deposited on Genbank with accession numbers of ON149839.1, OP597546.1, and ON521125.1 for L. europaeum L., L. shawii, and L. schweinfurthii var. aschersonii, respectively. The sequences showed variation in the GC content between the studied species of 63.6% in L. europaeum, 61.53% in L. shawii, and 63.55% in L. schweinfurthii var. aschersonii. Sixty-two amplified fragments including 44 polymorphic fragments with a ratio of 70.97% were obtained in SCoT analysis and unique amplicons in L. europaeum L., shawii, and L. schweinfurthii var. aschersonii of 5, 11, and 4 fragments. Thirty-eight compounds were identified with an obvious fluctuation in the species’ extracts with GC-MS analysis profiling. Twenty-three of them are distinguishing chemicals that could help in identifying the extracts of the studies species chemically. The present study succeeded in presenting alternative clear, various, and diverse characters for distinguishing between L. europaeum, L. shawii, and L. schweinfurthii var. aschersonii.